The first football books published in Spain (1900-1919) - Torrebadella-Flix, Xavier; Nomdedeu-Rull, Antoni (Revista General de Información y Documentación, 2015)
This article aims to chronologically expose around football literature published in Spain in the first two decades of the twentieth century in order to validate its contribution to the creation and implementation of this sport in Spain. The study is developed through the use of resources and techniques of historical analysis about the treatment of the original documentary sources. The results show that, at the origins and implementation of football in Spain during the first two decades of the twentieth century, the specialized publishing around this sport represented an essential reference among the first fans to raise awareness and to develop the technical fundamentals of the game. Although football literature was limited and criticized due to its technical simplicity, it provided a valuable service to all the neophytes who tried to get started in this popular English sport. Likewise, football generated the most important literature of the gymnastic-sports movement of the early twentieth century, which helps us today to interpret the development of Spanish football.